Institutos federais, educação e desenvolvimento: o caso do IFTM e suas formas de inserção na sociedade - Vasconcellos, Inaê Soares de (2017)
The work investigates the relationship between the public policy of the Federal Institutes of Education, Science and Technology, PT governments that created them, and structural conditions of Brazilian society that influence policy and governments. The central hypotheses are that a) the Federal Institutes constitute a strategic component of the neodevelopmental project of PT governments; B) the policy of Federal Institutes does not have the proper accompaniment in their conduct, by the federal government or society. In Chapter 1, the analysis is constructed based on a bibliographical review and analysis of PT governments in the light of the references on developmentalism. In Chapter 2, the analyzis is about the force- ideas that most influence the politics of Professional and Technological Education from the second half of the twentieth century. In the same chapter, an analysis of the Federal Institutes as they are produced as a strategy of the neodevelopmental project of the PT governments. In Chapter 3, the task goes to case study, the Instituto Federal do Triângulo Mineiro seeking there the expressions - or not - of the relations established between social structures, governments and ideas presented in previous chapters. In the concluding remarks, it is concluded that the structure of Brazilian fragile democracy impacts on institutional relations in the IFTM and results in insuficient dialogue about the characteristics and purposes - eminently political, as it is intrinsic to public policies - that are found in the Law of Creation of Federal Institutes.